2010
DOI: 10.1021/nn901825y
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Electrochemical Capacitors Based on Ordered Mesoporous Silicon Carbide-Derived Carbon

Abstract: Microporous carbons, produced by selective etching of metal carbides in a chlorine-containing environment, offer narrow distribution of micropores and one of the highest specific capacitances reported when used in electrical double layer capacitors (EDLC) with organic electrolytes. Previously, the small micropores in these carbons served as an impediment to ion transport and limited the power storage characteristics of EDLC. Here we demonstrate, for the first time, how the preparation and application of templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
310
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(333 citation statements)
references
References 46 publications
21
310
1
1
Order By: Relevance
“…As a result, the voltage shows a larger variation with charge, and the capacitance decreases. Our findings also help to explain the excellent high-current performances of hierarchical meso/micropore structures 41 and zeolitetemplated carbons with pore connectivity in three dimensions. 44 9…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…As a result, the voltage shows a larger variation with charge, and the capacitance decreases. Our findings also help to explain the excellent high-current performances of hierarchical meso/micropore structures 41 and zeolitetemplated carbons with pore connectivity in three dimensions. 44 9…”
mentioning
confidence: 55%
“…21 Kondrat et al have suggested that ideally the carbon pores would be initially empty of ions (ionophobic pores) to facilitate fast charging, 16,24,40 Our measurements on carbons with different pore sizes help to explain previous electrochemical studies of charging dynamics. 1,[41][42][43] For carbons with smaller average pore sizes and fewer mesopores (< 2 nm), the capacitance decreased more rapidly as the current density was increased.…”
mentioning
confidence: 99%
“…This behavior is in accordance with its low electronic conductivity and resistance to ion transport within the porous structure as was confirmed in the EIS measurements (see Figure 4c). The rate capability of the activated microspheres compares well with that of advanced porous carbons, including hierarchical porous carbons [55][56][57][58]. The stability of these materials in organic electrolyte was evaluated by charge-discharge and N-CSA-700 at their maximum working voltage window in volumetric units.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The interaction between PPy and CDC in the composite was investigated using Raman spectrometry. It is known from literature that typical disordered carbons as CDC hold disorder-induced D-band associated with a double-resonance Raman process located at 1340 cm -1 [29,30]. The position of this band may vary, depending on the structure of the disordered carbon and the presence of impurities or functional groups.…”
Section: Synthesismentioning
confidence: 99%